2021
DOI: 10.1016/j.eswa.2021.114997
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy case-based reasoning approach for finding COVID-19 patients priority in hospitals at source shortage period

Abstract: In this research article, we introduced an algorithm to evaluate COVID-19 patients admission in hospitals at source shortage period. Many researchers have expressed their conclusions from different perspectives on various factors such as spatial changes, climate risks, preparedness, blood type, age and comorbidities that may be contributing to COVID-19 mortality rate. However, as the number of people coming to the hospital for COVID-19 treatment increases, the mortality rate is likely to increase due to the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Contou et al 25 have reported that median survival time, of 73 out of 153 patients admitted to ICU’s being critically ill due to refractory respiratory failure, shock with multiorgan failure, cardiac death, and neurological death, was 14 days. Geetha et al 26 have shown that the average time to peak the severity of symptoms, since the symptoms began, was 7 days on average. Garcia-Garcia et al’s 18 estimations of the probability distribution of death since illness yielded a mean of 14.5 days and a median of 13.2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Contou et al 25 have reported that median survival time, of 73 out of 153 patients admitted to ICU’s being critically ill due to refractory respiratory failure, shock with multiorgan failure, cardiac death, and neurological death, was 14 days. Geetha et al 26 have shown that the average time to peak the severity of symptoms, since the symptoms began, was 7 days on average. Garcia-Garcia et al’s 18 estimations of the probability distribution of death since illness yielded a mean of 14.5 days and a median of 13.2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Its applications are covered, for instance, by Nasser et al [73] and Tayali and Timor [74]. The application of other methods can be found in the research of Geetha et al [75], Narayanamoorthy et al [76] and Ramya [77].…”
Section: Selected Methods For Weighting Indicatorsmentioning
confidence: 99%
“…Contou et al 16 have reported that the median survival time, of 73 out of 153 patients admitted to ICU's being critically ill due to refractory respiratory failure, shock with multiorgan failure, cardiac death, and neurological death, was 14 days. Geetha et al 17 have shown that the average time to peak the severity of symptoms, since the symptoms began, was 7 days on average. Hence, we take a conservative 7 to 14 day window for t De and t Ds from the day of showing up symptoms for individuals, identified as new cases, C, to be subjected to death.…”
Section: Models and Methodsmentioning
confidence: 99%